A Comparative Analysis Of Active And Passive Investing Strategies In Dana Pensiun XYZ (Dapen XYZ) - Novryansyah, Ryan; Erman Sumirat (CV. AFDIFAL MAJU BERKAH, 2024)
The study aims to provide a comprehensive comparative analysis of active vs. passive investment strategies in the context of pension funds, aimed at providing insights into the dynamic discourse surrounding active and passive investment. Through an exploration of empirical data and scientific discourses, the study highlights the potential benefits and limitations of each strategy, ultimately contributing to the informed decision-making process for pension fund managers. The study will also use the Markowitz model and efficient boundary methods to analyze and optimize investment strategies, focusing on risk, cost and cost management, and investment strategy. The analysis will also provide insights that can be done for fund managers to target higher investment returns, in terms of influencing company decisions and behavior to implement long-term investment strategies by reallocating some assets to other investment strategies